DAMPAK CHATGPT PADA KETERAMPILAN BERPIKIR KRITIS: STUDI KASUS MAHASISWA TEKNIK INFORMATIKA STMIK MERCUSUAR BEKASI - Rinaldo, Rinaldo (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
The advent of generative artificial intelligence has reshaped higher education dynamics, particularly in technology-related study programs. This study aims to analyze the impact of ChatGPT usage on the critical thinking skills of Informatics Engineering students at STMIK Mercusuar Bekasi. A quantitative approach with a descriptive-analytical survey design was employed. Data were collected using a Likert-scale questionnaire distributed online to 57 respondents in July 2025 and analyzed with descriptive statistics and index calculations. The results indicate that students massively adopt ChatGPT to support productivity, accelerate task completion, and broaden their knowledge through new information access. However, its direct impact on enhancing fundamental critical thinking skills is perceived to be relatively limited. This finding suggests the presence of a cognitive offloading phenomenon, where students distinguish between external assistance in the thinking process and the development of independent critical thinking skills. The study highlights the necessity of targeted pedagogical strategies to ensure that ChatGPT utilization not only improves efficiency but also strengthens students’ critical thinking abilities sustainably.